Physicians’ attitudes and acceptance towards artificial intelligence in medical care: a qualitative study in Germany - Sarah Negash; Jana Gundlack; Charlotte Buch; Timo Apfelbacher; Jan Schildmann; Thomas Frese; Jan Christoph; Jan Christoph; Rafael Mikolajczyk (Frontiers in Digital Health)
BackgroundThe role of artificial intelligence (AI) in medicine is rapidly expanding, with the potential to transform physicians’ working practices across various areas of medical care. As part of the PEAK project (Perspectives on the Use and Acceptance of Artificial Intelligence in Medical Care) this study aimed to investigate physicians’ attitudes towards and acceptance of AI in medical care.MethodsBetween June 2022 and January 2023 eight semi-structured focus groups (FGs) were conducted with general practitioners (GPs) recruited from practices in the region of Halle/Leipzig, Germany, via email and postal mail, as well as with university hospital physicians from Halle and Erlangen, recruited via email. To conduct the FGs, a topic guide and a video stimulus were developed, including a definition of AI and three potential applications in medical care. Transcribed FGs and field notes were analyzed using qualitative content analysis.Results39 physicians participated in eight FGs, including 15 GPs [80% male, mean age 44 years, standard deviation (SD) 10.4] and 24 hospital physicians (67% male, mean age 42 years, SD 8.6) from specialties including anesthesiology, neurosurgery, and occupational medicine. Physicians’ statements were categorized into four themes: acceptance, physician–patient relationship, AI development and implementation, and application areas. Each theme was illustrated with selected participant quotations to highlight key aspects. Key factors promoting AI acceptance included human oversight, reliance on scientific evidence and non-profit funding. Concerns about AI's impact on the physician-patient relationship focused on reduced patient interaction time, with participants emphasizing the importance of maintaining a human connection. Key prerequisites for AI implementation included legal standards, like clarifying responsibilities and robust data protection measures. Most physicians were skeptical about the use of AI in tasks requiring empathy and human attention, like psychotherapy and caregiving. Potential areas of application included early diagnosis, screening, and repetitive, data-intensive processes.ConclusionMost participants expressed openness to the use of AI in medicine, provided that human oversight is ensured, data protection measures are implemented, and regulatory barriers are addressed. Physicians emphasized interpersonal relationships as irreplaceable by AI. Understanding physicians’ perspectives is essential for developing effective and practical AI applications for medical care settings.